Studies on Novel bacteriocin like inhibitory substance (BLIS) from microalgal symbiotic Vibrio spp MMB2 and its activity against aquatic bacterial pathogens - Selvendran M and Michael Babu M. (Journal of Applied Pharmaceutical Science, 2013)
The present study was aimed to isolate the antagonistic bacteria from marine microalgal sample (Chlorella salina), the isolated bacterial strains were identified, screened for their bioactivity against the aquatic pathogens, to extract and characterize the compounds produced by antagonistic bacteria. Among the isolates Vibrio sp.MMB2 strain and Pseudomonas sp. had good antagonistic property against all tested pathogens. The maximum biogenic activity was occurred at the stationary phase culture. The metabolites extracted from Vibrio sp. MMB2 was showed highest zone of inhibition against A.hydrophylla. One active fraction was isolated by TLC. The functional group was identified through FTIR analysis, the bacterial metabolites contains Nitrogenous compound as a functional groups. The Partially purified CFNS (bacteriocin) of Vibrio sp. MMB2 was showed two distinct bands on SDS-PAGE, its high molecular weight of antimicrobial peptides. The bacterial metabolites effectively controlled the pathogens at broad range, to compare commercial antibiotics.
Keywords: Antagonistic bacteria, Biogenic activity, metabolite